Solar Powered Street Lighting - Arshad, Muhammad Syarif (Universiti Sains Malaysia, 2017)
Solar Powered Street Lights is a project that can help Universiti Sains Malaysia School of Electrical & Electronic (SEE) in electricity cost savings by implementing the use of existing solar PV system. Because the cost of electricity to the national grid Tenaga Nasional Berhad (TNB), which continues to increase, the system is able to maximize cost savings for SEE. Solar energy collected during the day will be converted into electricity to charge the battery. Electricity charged will be connected and used to power the lights around the SEE parking area at night. Taking into account all important aspects that help to optimize energy saving, this system is proven to reduce electricity costs. System data such as the power consumption by the load, battery charging rates, and other relevant data is measured. From the measured data, calculations and analysis were performed to determine the actual performance of the system. Proper wiring connections between solar PV systems and light poles grid around the SEE parking lot have been executed. Appropriate types of light bulbs have also been installed on light poles around the SEE parking lot. This type of light bulbs consumes electricity at a rate that is not too high and generate an appropriate level of visibility at night. As a result, the implementation of this system could save as much as RM 462.86 for the cost of monthly electricity bills incurred by the SEE.